Application of palladium-catalyzed aryl C–H alkylation in total synthesis of (−)-berkelic acid. Issue 1 (13th November 2020) - Wang, Hui-Hong; Wang, Xiao-Dong; Cao, Fei; Gao, Wei-Wei; Ma, Shu-Meng; Li, Zhao; Deng, Xue-Mei; Shi, Tao; Wang, Zhen
Abstract : Total synthesis of the isochroman natural product (–)-berkelic acid. Abstract : An unprecedented palladium(ii )-catalyzed ortho -alkylation of N -methoxybenzamide with epoxides has been applied to the total synthesis of the isochroman natural product (–)-berkelic acid. Combining this strategy with a well documented spiroacetalization cascade reaction, (–)-berkelic acid is obtained in 13.9% overall yield with the longest linear sequence of 11 steps. The results of preliminary biological studies on the synthesized natural product and its analogues are also reported.